Exposure to fine particulate matter (PM2.5) hampers myelin repair in a mouse model of white matter demyelination. (May 2021) - Parolisi, Roberta; Montarolo, Francesca; Pini, Alessandro; Rovelli, Sabrina; Cattaneo, Andrea; Bertolotto, Antonio; Buffo, Annalisa; Bollati, Valentina; Boda, Enrica
Abstract: Epidemiological studies show a strong association between exposure to air pollution – and particularly to particulate matter (PM) -, increased prevalence of Multiple Sclerosis (MS) and higher rates of hospital admissions for MS and MS relapses. Besides having immunomodulatory effects and sustaining a systemic oxidative-inflammatory response, PM may participate in MS pathogenesis by targeting also Central Nervous System (CNS)-specific processes, such as myelin repair. Here we show that, in a mouse model of lysolecithin-induced demyelination of the subcortical white matter, post-injury exposure to fine PM hampers remyelination, disturbs oligodendroglia differentiation dynamics and promotes astroglia and microglia reactivity. These findings support the view that exposure to fine PM can contribute to demyelinating pathologies by targeting the endogenous regenerative capability of the CNS tissue. Graphical abstract: Image 1 Highlights: PM2.5 exposure hampers myelin repair in a mouse model of demyelination. PM2.5 exposure disturbs post-injury oligodendroglia differentiation dynamics. PM2.5 exposure sustains astroglia and microglia reactivity.